Information asymmetry around operational risk announcements - Barakat, Ahmed; Chernobai, Anna; Wahrenburg, Mark (Elsevier, 2014)
Operational risk incidences are likely to increase the degree of information asymmetry between firms and investors. We analyze operational risk disclosures by US financial firms during 1995–2009 and their impact on different measures of information asymmetry in the firms’ equity markets. Effective spreads and the price impact of trades are shown to increase around the first announcements of such events and to revert after the announcement of their settlement. This is especially pronounced for internal fraud and business practices related events. Market makers respond to higher information risk around the first press cutting date by increasing the quoted depth to accommodate an increase in trading volumes.